2011
DOI: 10.1590/s1678-77572011000200008
|View full text |Cite
|
Sign up to set email alerts
|

HOXB5 expression in oral squamous cell carcinoma

Abstract: Human HOX genes encode transcription factors that act as master regulators of embryonic development. They are important in several processes such as cellular morphogenesis and differentiation. The HOXB5 gene in particular has been reported in some types of neoplasm, but not in oral cancer.ObjectiveThe present study investigated the expression of HOXB5 in oral squamous cell carcinoma (SCC) and in non-tumoral adjacent tissues, focusing on verifying its possible role as a broad tumor-associated gene and its assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…As a member of the HOX gene family, the HOXB cluster plays important roles in many tumours . HOXB5, a protein‐coding gene in the HOXB cluster, is upregulated in oral squamous cell carcinoma . HOXB5 also plays significant roles in the progression of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the HOX gene family, the HOXB cluster plays important roles in many tumours . HOXB5, a protein‐coding gene in the HOXB cluster, is upregulated in oral squamous cell carcinoma . HOXB5 also plays significant roles in the progression of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…HOX genes have been described as deregulated in several cancers including leukemia, colon, skin, prostate, breast, ovary, and, more recently, in oral cavity cancer (9 -17). In addition, some studies observed the aberrant expression of various HOX genes in oral squamous cell carcinoma (OSCC) and esophageal squamous cell carcinoma (ESSC) (10,18,19). However, the specific mechanisms by which HOX genes contribute to the development of cancer have not been completely described.…”
mentioning
confidence: 99%
“…QPCR and immunohistochemistry), and which has been demonstrated in 2 different studies. The findings of this review for head and neck [24,[28][29][30][31][32][33][34][35][36], oesophageal [37,38], gastric [39,40], colorectal [41], pancreatic [42], hepatic [41], lung [43][44][45][46], breast [47], bladder [48,49], renal [23], prostate [50,51], and ovarian cancer [52][53][54] are summarized in Fig 1 and (Fig 1). These distinct, tumour-specific expression profiles make HOX genes potential markers of CTCs.…”
Section: Hox Genes In Cancermentioning
confidence: 99%